Sulfur dioxide fumigation alone or in combination with CO2-enriched atmosphere extends the market life of highbush blueberry fruit - Goulas, Vlasios; Cantín, Celia M.; Minas, Ioannis S.; Jiménez, Manuel; Michailides, Themis J.; Crisosto, Carlos H.; Manganaris, George A. (My University, 2012)
The combined effect of sulfur dioxide (SO 2) fumigation and different carbon dioxide (CO 2)-enriched atmospheres (3% O 2+3, 6, 12, or 24% CO 2) on quality attributes, postharvest decay, phytochemical content, and antioxidant capacity of eight fresh blueberry cultivars (Vaccinium corymbosum L.) was determined. The SO 2 treatments did not harm berry quality, but did significantly reduce decay incidence, especially when it was followed by storage in elevated CO 2 atmospheres (>6%). However, very high CO 2 atmospheres (24%) induced fruit softening and 'off-flavors'. Botrytis and Alternaria spp. were the dominant fungal pathogens causing decay of blueberries during storage, but differences in the species of decay microorganisms were found among cultivars. Postharvest strategies that included SO 2 fumigation and/or enriched CO 2 atmospheres did not negatively affect phytochemical content or antioxidant activity of the fruit; however, the polyphenolic content and total antioxidant activity varied greatly among cultivars. Overall, SO 2 fumigation followed by controlled atmosphere storage (3% O 2+6 or 12% CO 2) is a promising postharvest strategy for fresh blueberries to reduce decay, extend market life, and maintain high nutritional value
Keywords: Phytochemicals; Polyphenols; Sensory evaluation; Alternaria; Botrytis; Vaccinium; Atmosphere; Blueberries